2020
DOI: 10.1186/s12885-020-06953-8
|View full text |Cite
|
Sign up to set email alerts
|

Combination of preoperative neutrophil-lymphocyte ratio, platelet-lymphocyte ratio and monocyte-lymphocyte ratio: a superior prognostic factor of endometrial cancer

Abstract: Background: The preoperative peripheral blood neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and monocyte-lymphocyte ratio (MLR) have been reported to be associated with the prognosis of various cancers but are always discussed separately. The aim of this study is to bring the combination of NLR, PLR and MLR into the prognostic assessment system of endometrial cancer (EC) and establish a nomogram to provide an objective prediction model for clinical decisions. Methods: A total of 1111 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 33 publications
0
46
1
Order By: Relevance
“…Recent studies indicate that NLR might be a useful diagnostic and prognostic marker for different cancers. 11,[32][33][34][35][36] A high NLR represents an increase in immunosuppressive status, and reportedly, is associated with poor survival in esophageal, gastric, colorectal, lung, breast cancer, and urologic cancers. 32,34 Regarding gynecologic malignancies, high NLR is associated with poor clinical outcomes in ovarian, endometrial, and cervical cancer, and in uterine sarcoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies indicate that NLR might be a useful diagnostic and prognostic marker for different cancers. 11,[32][33][34][35][36] A high NLR represents an increase in immunosuppressive status, and reportedly, is associated with poor survival in esophageal, gastric, colorectal, lung, breast cancer, and urologic cancers. 32,34 Regarding gynecologic malignancies, high NLR is associated with poor clinical outcomes in ovarian, endometrial, and cervical cancer, and in uterine sarcoma.…”
Section: Discussionmentioning
confidence: 99%
“…11,[32][33][34][35][36] A high NLR represents an increase in immunosuppressive status, and reportedly, is associated with poor survival in esophageal, gastric, colorectal, lung, breast cancer, and urologic cancers. 32,34 Regarding gynecologic malignancies, high NLR is associated with poor clinical outcomes in ovarian, endometrial, and cervical cancer, and in uterine sarcoma. 11,32,33,35 In a metaanalysis conducted by Wu et al in cervical cancer, an elevated NLR was found to be closely associated with poor clinical outcomes and unfavorable clinicopathological factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…119 Kadan et al found that the mean NLR was higher in the node-positive group compared with node-negative patients (3.4 vs 2.9, respectively); however the difference was not statistically significant. 120 Cong 121 Eo et al analyzed 255 females with newly diagnosed endometrial cancer and reported an LMR cutoff value of 3.28 for both DFS and OS. 122 The 5-year DFS rates in the LMR-low and LMR-high groups were 64.5% and 93.9%, respectively (p<0.0001).…”
Section: Endometrial Cancermentioning
confidence: 99%
“…The combined indicator, high NLR + high PLR + high LMR (HR: 4.34, 95% CI: 2.54–7.42; p<0.001), showed the highest prognostic value. 121 Eo et al analyzed 255 females with newly diagnosed endometrial cancer and reported an LMR cutoff value of 3.28 for both DFS and OS. 122 The 5-year DFS rates in the LMR-low and LMR-high groups were 64.5% and 93.9%, respectively (p<0.0001).…”
Section: Systemic Inflammatory Reaction In Neoplasms Of the Female Genital Organsmentioning
confidence: 99%